Unrelated parallel machines scheduling with dependent setup times in textile industry. (December 2022) - Berthier, A.; Yalaoui, A.; Chehade, H.; Yalaoui, F.; Amodeo, L.; Bouillot, C.
Abstract: The problem tackled in this paper is an unrelated parallel machines scheduling problem with machine and sequence dependent setup times, machine eligibility and different resource types constraints. This subject is inspired from a textile industry partner case. The different characteristics of this problem have never been combined as it is depicted in this paper. Two resolution methods are exposed. A new mathematical programming is proposed to have an exact resolution approach of this complex problem. An improved genetic algorithm (GA) with dedicated operators is also presented in order to solve the industrial case in a reasonable computational time. Highlights: Real case study from textile industry and knitting workshop. Use of mathematical programming to solve an unrelated parallel machines scheduling. Resolution on CPLEX-ILOG solver. Improvement of a genetic algorithm with real problem dedicated operators.